Penerapan Model Pembelajaran Kelas Rangkap (PKR) Sebagai Upaya Pemenuhan Guru di SDN 068 Manganan Kecamatan Rongkong - Muh. Idel; Edhy Rustan; Hisbullah (Socratika: Journal of Progressive Education and Social Inquiry, 2025)
This study examines the implementation of multi-grade learning at SDN 068 Manganan, Rongkong sub-district, identifying the constraints and factors that influence its implementation. The research objectives are (1) to evaluate teacher fulfillment at SDN 068 Manganan, (2) to analyze the implementation of multi-grade classes at the school, and (3) to understand how the implementation of multi-grade classes meets teacher needs. This study used a qualitative approach with data collection through observation, interviews, and documentation in the field. The results showed that the fulfillment of multi-grade classes was influenced by the geographical location of the school and the lack of educators. The implementation of multi-grade classes uses the PKR-221 model with two different classes in one room. The main challenges in fulfilling teachers' needs include the lack of human resources and adequate learning facilities, requiring improvement and attention from teachers and the local government. The implication of this study is the need for more intensive efforts in improving human resources and learning facilities in schools that implement multi-grade learning to support the effectiveness and quality of learning, one of the most important is the recruitment of ASN teachers should be given to communities in the Rongkong District area.